rTMS Implementation in ELFT (East London Foundation Trust): A Prospective Clinical Study - Areej Rasheed; Harith Ali; Asho Oommen; Daniel Allen; Geoff Lawrence-Smith (BJPsych Open, 2025)
Aims: To evaluate the effectiveness and safety of repetitive transcranial magnetic stimulation (rTMS) in treating treatment-resistant depression (TRD), with a focus on changes in depression severity measured by the Montgomery–Åsberg Depression Rating Scale (MADRS) and the Hamilton Depression Rating Scale (HAMD).